2020
DOI: 10.3390/fermentation6030084
|View full text |Cite
|
Sign up to set email alerts
|

Side-by-Side Comparison of Clean and Biomass-Derived, Impurity-Containing Syngas as Substrate for Acetogenic Fermentation with Clostridium ljungdahlii

Abstract: Syngas, the product of biomass gasification, can play an important role in moving towards the production of renewable chemical commodities, by using acetogenic bacteria to ferment those gaseous mixtures. Due to the complex and changing nature of biomass, the composition and the impurities present in the final biomass-derived syngas will vary. Because of this, it is important to assess the impact of these factors on the fermentation outcome, in terms of yields, productivity, and product formation and ratio. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 46 publications
1
32
0
Order By: Relevance
“…Rückel et al [50] found that NH 3 and H 2 S increased both growth and alcohol formation (ethanol, 1-butanol and 1-hexanol) during syngas fermentation by Clostridium carboxidivorans. On the other hand, Xu and Lewis [51] showed that NH 3 is rapidly converted to ammonium ion (NH 4 + ) in the fermentation media and the accumulated NH 4 + inhibits hydrogenase activity and cell growth of acetogenic bacteria. It seems that there is a microbial tolerance for these substances [10].…”
Section: Syngas Impuritiesmentioning
confidence: 99%
“…Rückel et al [50] found that NH 3 and H 2 S increased both growth and alcohol formation (ethanol, 1-butanol and 1-hexanol) during syngas fermentation by Clostridium carboxidivorans. On the other hand, Xu and Lewis [51] showed that NH 3 is rapidly converted to ammonium ion (NH 4 + ) in the fermentation media and the accumulated NH 4 + inhibits hydrogenase activity and cell growth of acetogenic bacteria. It seems that there is a microbial tolerance for these substances [10].…”
Section: Syngas Impuritiesmentioning
confidence: 99%
“…Although studies have been performed that focused on the usage of real, biomass-derived synthesis gases, currently few studies have investigated the influences of the individual trace components to give further insight into the role of certain trace components (Datar et al, 2004;Ahmed et al, 2006;Xu et al, 2011;Infantes et al, 2020). The toxicity of HCN on the anaerobic bacteria C. ljungdahlii has already been analyzed and identified as a critical factor for the growth of anaerobic microorganisms with inhibiting effects at 1.6 mg L −1 and a strong toxic effect at concentrations of 0.065 g L −1 KCN in anaerobic shanking flasks (Oswald et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This study aims to close the gap in the existing literature concerning the effects of individual trace impurities in syngases. Studies so far focused solely on the effects of syngas from gasification of biogenic residues and found inhibiting effects without clearly identifying the components responsible for the effects (Infantes et al, 2020;Liakakou et al, 2021). Also, most studies focused on C. ljungdahlii as a typical model organism for acetogenic bacteria, while this study used C. carboxidivorans as a promising acetogen for the production of longer chain alcohols.…”
Section: Introductionmentioning
confidence: 99%
“…Contaminants such as tar, cyanide and other molecules are recognized as one of the biggest obstacles for direct syngas fermentation. These molecules can be present in concentrations shown to hinder microbial growth, significantly affecting overall yields and productivities [6][7][8][9][10][11][12][13][14]. For example, the presence of tar in crude syngas produced by lignin gasification was shown to induce cell dormancy and influence the redistribution of ethanol and acetic acid production by Clostridium carboxidivorans P7 T and Clostridium ragsdalei P11 [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the presence of tar in crude syngas produced by lignin gasification was shown to induce cell dormancy and influence the redistribution of ethanol and acetic acid production by Clostridium carboxidivorans P7 T and Clostridium ragsdalei P11 [15,16]. Fortunately, some of these inhibitory effects may be mitigated by gradually adapting microbial cultures to crude syngas, prior to fermentation [9,10,17].…”
Section: Introductionmentioning
confidence: 99%